Identification of Acid-Based Concept Understanding Using the Assessment of A Two-Tier Multiple Choice Diagnostic Instrument - Lisa Ariyanti Pohan; Syahwin Syahwin (Proceedings of AICS - Social Sciences, 2017)
Mastery of concepts in chemistry lessons it is important to note, byteachers of chemistry. Therefore, this study was aimed to evaluate the concept of understanding acid -base using a multiple-choice assessment type two tier. So that teachers are able to measure the students ' understanding about the mastery of acid-base conceptas reference materials for teachers to continueto correct the learning in the classroom. A number of 15 items about the concept of acid-base was designedusing multiple choice two tier test tested to 11th graders in the even semester. The method used in this study using descriptive qualitative. The research was conducted in senior high school 19 Medan with population 159. The sampling technique was done by random sampling. Data analysis technique used description of data obtained from result of student answer. The results of the data analysis obtained as amount as 47% or there are seven items which answered correctly in the first tierwith the lowestcategory, 47% or there are seven items which answered correctly in both tierswith medium category, and only one question answered correctly on both tiers with high category. Percentage of students' understanding of the concept of acid-base using two tier diagnostic tests is 35 people or 47% in the low category, 40 persons or 53% in the medium category, while the highercategory is 0%. Keywords: identification,chemistry assessment, two-tier tests, acids and bases concept.